2003
DOI: 10.1111/j.1462-2920.2003.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the response regulator gene gacA in Pseudomonas species

Abstract: The response regulator gene gacA influences the production of several secondary metabolites in both pathogenic and beneficial Pseudomonas spp. In this study, we developed primers and a probe for the gacA gene of Pseudomonas species and sequenced a 425 bp fragment of gacA from ten Pseudomonas strains isolated from different plant-associated environments. Polymerase chain reaction analysis and Southern hybridization showed that gacA is highly conserved within the genus Pseudomonas: multiple strains of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 55 publications
2
56
0
4
Order By: Relevance
“…However, DGGE with specific primers for pseudomonads documented a strong shift in the diversity among these specific Gammaproteobacteria, a result consistent with findings of Rønn et al (2002) who studied effects of protozoa on bacterial communities in soil organic patches. The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…However, DGGE with specific primers for pseudomonads documented a strong shift in the diversity among these specific Gammaproteobacteria, a result consistent with findings of Rønn et al (2002) who studied effects of protozoa on bacterial communities in soil organic patches. The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…O DNA genômico foi extraído pelo método do CTAB modificado (SOUZA et al, 2003). O gene 16S rDNA foi amplificado via PCR, utilizando-se os primers 8fn (5'-AGA GTT TGA TCC TGG CTC AG-3') e 1429r (5'-ACG GCT ACC DTT GTT ACG ACT T-3') (ESIKOVA et al, 2002).…”
Section: (Recebido Em 17 De Abril De 2007 E Aprovado Em 3 De Junho Deunclassified
“…O gene 16S rDNA foi amplificado via PCR, utilizando-se os primers 8fn (5'-AGA GTT TGA TCC TGG CTC AG-3') e 1429r (5'-ACG GCT ACC DTT GTT ACG ACT T-3') (ESIKOVA et al, 2002). As reações de PCR foram feitas conforme Souza et al (2003). Os produtos amplificados foram separados em géis de agarose de acordo com métodos descritos por Sambrook & Russel (2001).…”
Section: (Recebido Em 17 De Abril De 2007 E Aprovado Em 3 De Junho Deunclassified
“…O DNA genômico foi extraído pelo método do CTAB modificado, como descrito por Souza et al (2003). O gene 16S rDNA foi amplificado via PCR, utilizando-se os primers 8fn (5'-AGA GTT TGA TCC TGG CTC AG-3') e 1429r (5'-ACG GCT ACC DTT GTT ACG ACT T-3') (Esikova et al, 2002).…”
Section: Identificação Dos Isolados Mais Eficientesunclassified
“…O gene 16S rDNA foi amplificado via PCR, utilizando-se os primers 8fn (5'-AGA GTT TGA TCC TGG CTC AG-3') e 1429r (5'-ACG GCT ACC DTT GTT ACG ACT T-3') (Esikova et al, 2002). As reações de PCR foram feitas como descrito por Souza et al (2003). Os produtos amplificados foram separados em géis de agarose, de acordo com métodos descritos por Sambrook & Russel (2001).…”
Section: Identificação Dos Isolados Mais Eficientesunclassified